Every Breath You Take—Every Dollar You’ll Make: The Long-Term Consequences of the Clean Air Act of 1970 - Isen, Adam; Rossin-Slater, Maya; Walker, W. Reed (Journal of Political Economy, 2017)
This paper examines the long-term impacts of in-utero and early childhood exposure to ambient air pollution on adult labor market outcomes. We take advantage of a new administrative data set that is uniquely suited for addressing this question because it combines information on individuals ’ quarterly earnings together with their counties and dates of birth. We use the sharp changes in ambient air pollution concentrations driven by the implementation of the 1970 Clean Air Act Amendments as a source of identifying variation, and we compare cohorts born in counties that experienced large changes in total suspended particulate (TSP) exposure to cohorts born in counties that had minimal or no changes. We find a significant relationship between TSP exposure in the year of birth and adult labor market outcomes. A 10 unit decrease in TSP in the year of birth is associated with a 1 percent increase in annual earnings for workers aged 29-31. Most, but not all, of this effect is driven by an increase in labor force participation. In present value, the gains from being born into a county affected by the 1970 Clean Air Act amount to about $4,300 in lifetime income for the 1.5 million individuals born into